IMPLEMENTATION OF COMMUNICATIVE APPROACHES IN THE PROCESS OF TEACHING ENGLISH IN GRADES 6-7 - Nizamova, G.U. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2022)
The main goal of the article is the formation and development of communicative competence in teaching a foreign language, fluency in the language through speech.The communicative method proposed in this article is intended as a means of teaching speaking for schoolchildren. It is quite understandable that the development of communicative method as an adequate teaching tool requires a clear understanding of what the purpose of the teaching is. Therefore, we first analyze this goal – speaking foreign language from different points of view. This will help answer the question of why the communicative method is necessary and what it is. I’ll discuss this in more detail in the discussion section. In conclusion, we note that when teaching both dialogical and group communication, the communicative teaching method plays an important role. We must use this teaching method in every lesson.
Keywords: communicative teaching method; dialogical and group communication; interactive teaching; communicative approach; English language